Predicting EFL Learners’ Self-Regulated Learning through Technology Acceptance Model: - - Yusup Supriyono; Francisca Maria Ivone; Dedi Heryadi; Lorna Beduya; Luis Luigi Eugenio A. Valencia (Universitas Islam Negeri (UIN) Syekh Wasil, Kediri, Indonesia, 2024)
The purpose of this study is to assess the perceived usefulness of technology (PUT), internet self-efficacy (ISE), and perceived ease of use of technology (PEUT), and self-regulated learning (SRL) of EFL student teachers who participated in technology-mediated English learning environment. After obtaining and validating the questionnaire adapted from several relevant sources, an online survey was conducted to 363 third- and fourth-year student teachers of the English education department in Indonesian universities who met the required criteria. SEM was performed to test three hypotheses about the causal relationship between variables. Due to the hypotheses tested, it is revealed that ISE and PEUT have a partially positive and significant effect on SRL, while PUT has a positive but insignificant effect on SRL. Additionally, it is determined that the exogenous variables (PEUT) is the most influential variable on the endogenous variables (SRL). These findings are expected to add to a body of knowledge, particularly in the development of learning autonomy in teacher education, and that ISE and PEUT, in particular, should be considered as important predictors of SRL in technological English learning setting.